IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT (TQM) - Rokhmah, Dewi; Mukaromah, Chaerunnisa Al; Adittian, Faiz (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to describe and analyze the implementation of Total Quality Management in SMA Negeri 1 Bumiayu. This study uses a qualitative approach with data collection techniques carried out using interviews, observation, and documentation. Sources of research data include school principals, deputy heads of curriculum, deputy heads of student affairs, deputy heads of infrastructure, heads of TU, teachers , TU staff, students, and student guardians. The results showed that the implementation of Total Quality Management in SMA Negeri 1 Bumiayu was said to be in accordance with the four main implementations in Total Quality Management, which included: 1. Continuous improvement, including providing training, focusing on facts or valid data in each policy, paying attention to the needs of students and parents, paying attention to good interpersonal cooperation, monitoring and evaluation; 2. Determining quality standards, including implementing standards according to what has been set by the government; 3. Cultural changes, including providing adequate tools or infrastructure as a step to maximize teacher performance, appreciating what teachers do as a form of humanizing humans to improve their performance by giving rewards and taking approaches as a form of strengthening relationships between leaders and members in improving quality education; 4. Maintaining relationships with customers, including optimizing services by providing responsive information search, increasing school comfort, establishing good closeness with internal and external customers, providing the best service, implementing a curriculum that fits the needs of students, providing adequate facilities and infrastructure , and adequate reading references.